A note on some strongly sequence spaces - Savas, Ekrem; Kilicman, Adem (Hindawi Publishing Corporation, 2011)
We introduce and study new sequence spaces which arise from the notions of generalized de la Vallée-Poussin means, invariant means, and modulus functions.